On patent legislation, patent enforcement and economic growth: empirical evidence from developed and developing countries - Papageorgiadis, Nikolaos; Alexiou, Constantinos; Nellis, Joseph G. (Inderscience, 2016)
This study investigates the long-term effects of national patent legislation and enforcement systems on the economic development of 42 countries. The econometric methodology that has been adopted involves the estimation of three different models, namely, the pooled, the fixed effects and the random effects models whilst the specification of the economic development regressions is a variant of the standard growth specifications encountered in relevant studies. The empirical analysis is conducted in the context of the time period following the imposition of trade-related aspects of intellectual property rights (TRIPs). The results show that the extension and strengthening of patent legislation resulting from TRIPs have had a negative impact on economic development. In contrast, stronger levels of patent enforcement have had a positive effect overall and particularly for developing economies while negative for developed economies.
Keywords: patent legislation; patent enforcement; TRIPs; economic growth